Multi-mode optimal operation of advanced adiabatic compressed air energy storage: Explore its value with condenser operation - Li, Guangkuo; Chen, Laijun; Xue, Xiaodai; Guo, Zhongjie; Wang, Guohua; Xie, Ningning; Mei, Shengwei (Energy (Oxford), 2022)
The weather-dependent renewable energy sources(RESs) and voltage stability performance associated with reactive power balance pose immense challenges to power systems' operation. Salt cavern advanced adiabatic compressed air energy storage(S-CAES) is one of the most promising options to cope with the emerging issues. Though S-CAES has been extensively studied, limited attention focuses on the value of its reactive power ancillary service. This paper presents a novel S-CAES condenser operation mode that consumes little compressed air and less heat for synchronization and warm-keeping while releasing reactive power by the turbine-generator unit's excitation system for voltage regulation. The merits of condenser mode are highlighted, and the accurate thermodynamic model of S-CAES with multi-parameter coupled charging/discharging power functions is developed. Then, an optimal dispatch model linking the part-load characteristics and multiple service requirements is proposed and further formulated as a mixed-integer linear programming(MILP) problem. Numerical simulation results indicate that S-CAES operating in condenser mode contributes its application in ancillary services markets, and neglecting the part-load characteristics will lead to overly optimistic or even infeasible dispatch results. The breakeven point of the peak-valley ratio is 1.725, below which S-CAES will not participate in the energy market. Besides, sensitivity analysis provides a primary reference for S-CAES's heat supplement optimization and the design of condenser compensation mechanisms in the power system with a high proportion of RESs. •A novel condenser operation mode of S-CAES is proposed.•S-CAES operating in condenser mode consumes little compressed air and less heat, contributing to its application in ancillary services markets.•The multi-mode optimal operation model of S-CAES with condenser mode is proposed.•Dispatch results with and without considering the part-load characteristics are compared.•The heat supplement strategies and condenser compensation mechanism are investigated.